Exploring the use of virtual construction to capture knowledge and reduce waste for residential projects - Johnson, Bradly Thomas, author (Colorado State University. Libraries, 2007)
Construction lags behind manufacturing in productivity, occupational safety, and construction quality is considered to be insufficient (Koskela, 2000). Additionally, cost has continued to increase faster than the rate of inflation preventing many Americans from realizing home ownership (Shiller, 2006). Many of the advancements in manufacturing can be traced to the Lean production techniques developed by Toyota Motors (Ohno, 1988; Womack, 1996). A current line of research in the construction industry is focused on infusing Lean production principles into construction. Lean construction has not been significantly diffused in the construction industry primarily because it is a set of guiding principles or theory rather than an established set of practices. Few project management tools have been developed on the foundation lean principles. Producers of most manufactured products experienced breakthrough advances in productivity due to the digital-based convergence of 3-D CAD representations and production processes. The 3-D model serves as the medium for communication and collaboration among project participants. Products are digitally created and produced seamlessly from concept through production (Kolarevic, 2003). This study used a mixed methods sequential exploratory design (case study and quasi-experiment) to investigate waste in the residential on-site framing process. A new set of construction documents founded on lean principles was developed and tested for effectiveness to reduce waste. Much of the waste in the residential framing process is associated with the information poor traditional construction documentation. This study provided insight into the waste activities associated with residential framing by identifying four information categories associated with the waste. These categories are, preference information, conflicting information, insufficient information, and hard to find and/or confusing information. A set of traditional construction documents (TCD) was compared to a set of new construction documents (NCD) produced from a 3-D model on construction time, construction quality (including accuracy), and framing experience. The results of the quasi-experiment showed a significant reduction in time and an increase in accuracy when using the NCD. The results also showed that quality (not including accuracy) was a function of experience. Overall, it was found that when crews used the NCD produced from a 3-D model, waste was reduced.
Keywords: housing; 3-D technology; studies; research; language; principles; documentation; plumbing; friendship; engineers; case studies; schedules; experiments; computer aided design (CAD); copyright; data collection; engineering; building information modeling; onsite